Calcium-dependent protein kinases in plant immunity: from calcium signaling to network integration - Deng, Lu; Ji, Simin; Wang, Gaopeng; Liu, Xiang (Frontiers in Plant Science, 2026)
In response to environmental stimuli, plants rapidly activate calcium signaling to initiate downstream responses. The transmission of calcium signals involves three primary processes: perception, decoding, and relay. Calcium-dependent protein kinases (CDPKs/CPKs), as key Ca2+ sensors, not only detect calcium signals but also respond to them by translating these signals into physiological activities within the cell. The influx of calcium ions (Ca2+) induced by pathogens triggers the conformational activation of cytosolic CPKs, which in turn enables the regulation of reactive oxygen species (ROS) production, MAPK cascades, transcriptional reprogramming, and hormone signaling. Acting as pivotal hubs in signal transduction, CPKs integrate diverse pathways to fine-tune the balance between growth and defense. We synthesize recent advances in understanding CPK-mediated immune mechanisms and their molecular crosstalk with other signaling networks. By highlighting emerging discoveries and unresolved questions, we provide a conceptual framework for exploiting CPKs to enhance durable and broad-spectrum disease resistance in crops.